Effect of Cyclophosphamide on miRNA-15a expression in EBV infected transformed B cell - Abdolreza Sotoodeh Jahromi; Mohammad Kargar; Maliheh Moradzadeh; Farshid Kafilzadeh; Marzieh Jamalidoust (فصلنامه دانشگاه علوم پزشکی جهرم, 2021)
Background: Despite advances in diagnosis and therapy of cancer, it is still the main cause of death worldwide. Cyclophosphamide is one of the major drugs for lymphoma treatment. However, the anti-lymphoma effects of cyclophosphamide on micro-RNA expression are still unclear, especially in B cell lymphomas. The aim of the present study was to evaluate the effect of cyclophosphamide on miRNA-15a genes expression in Epstein‐Barr‐Virus (EBV)-infected transformed B cell. Material and Methods: In this study, the effects of cyclophosphamide on CO 88BV59-1 LCL – an EBV infected transformed B cell was evaluated. The cells were treated with cyclophosphamide (0.05-50 µM), for 3 days. The cell viability and cytotoxicity were evaluated using MTT, and flow cytometry techniques, respectively. Also, miRNA-15a genes expression were determined by real-time PCR. Results: Cyclophosphamide significantly inhibited proliferation and induced cell death in the cell-line in a dose and time-dependent manner (P<0.05). There were no significant changes in the expression of miRNA-15a3p and miRNA-15a5p in treated cells compared to untreated cells (P>0.05). Conclusions: The results showed that cytotoxic effects of cyclophosphamide on CO 88BV59-1 LCL is not related to miRNA-15a3p and miRNA-15a5p expressions.